The clinical and biomarker approach to predict sepsis mortality in pediatric patients - Irene Yuniar; Mulya Rahma Karyanti; Nia Kurniati; Desti Handayani (Indonesian Pediatric Society, 2023)
Background Sepsis is a leading cause of pediatric morbidity and mortality. The prevalence of sepsis mortality in Indonesia varies between 22.5 to 52%. Objective To identify the clinical criteria for predicting sepsis mortality and evaluate the performance of the PELOD-2 score. Methods This retrospective cohort study included pediatric patients admitted to the emergency department or pediatric intensive care unit (PICU) of Cipto Mangunkusumo Hospital, Jakarta, Indonesia, from January 2015 to May 2020. Demographic characteristics (age and sex), clinical manifestations [nutritional status, presence of shock, need for intubation, source of infection, inotrope use, mean arterial pressure, pulse rate, respiratory rate, and Glasgow Coma Scale (GCS) score], laboratory [leukocyte, platelet, neutrophil, and lymphocyte counts, neutrophil-to-lymphocyte count ratio (NLCR), procalcitonin, C-reactive protein (CRP), and lactate profile], PELOD-2 score, and mortality data were recorded as outcomes. Results We analyzed data from 241 sepsis subjects. The overall mortality rate was 65%. Shock [OR 3.2 (95%CI 1.80 to -5.55, P<0.001)], GCS <9 [OR 2.4 (95%CI 1.30 to 4.23, P=0.005)], inotrope use [OR 3.1 (95%CI 1.74 to 5.5, P<0.001)], CRP >33.5 mg/L [OR 2.5 (95%CI 1.14 to 5.35, P=0.02)], and lactate level >2.85 [OR 2.1 (95%CI 1.02 to 4.56, P=0.04)] were considered significant predictors of mortality. A PELOD-2 cut-off score of >8 had optimal sensitivity (81.2%) and specificity (72.9%) to predict mortality, with an OR of 11.6 (95%CI 5.72 to 23.5, P<0.001). Conclusion Shock, GCS score, inotrope use, CRP, and lactate level can serve as clinical biomarkers to predict mortality in pediatric sepsis. A PELOD-2 score of >8 can predict mortality with reasonably good sensitivity and specificity.